The Difference of Chest Pain in Adult and Elderly Patients with Acute Myocardial Infarction - Widaryati, Widaryati; Pratama, Rendy Arya; Enaryaka, Enaryaka (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2023)
Chest pain in an acute attack of myocardial infarction cannot be underestimated because this pain will have a harmful impact on the patient. Pain is influenced by personality, life stress, social economic factor, cognitive, and psychology factor. There is no study comparing chest pain between adult and elderly patients with coronary artery disease. Thus, this study to compare chest pain in patients with acute myocardial infarction in adults and the elderly. This research is a quantitative analytic study with a documentation study. With the purposive sampling technique, the number of samples in this study was 68 respondents. The statistical analysis employed the Mann Withney test. Out of total participant ( n=68), 72,1 % were elderly, 60,3 % were male and 79,4 % were STEMI. The results were obtained from the pain scale in adults with a mean value of 54.11 and a mean value at the elderly age 26.90 with a value of p (0.000). There is a significant difference between myocardial infarction pain in adults and acute myocardial infarction pain in the elderly. Adult more high intensity of pain than elderly patients. This study recommended that health workers so provide serious treatment for chest pain patients in elderly althaought the pain is not serious.